The role and functions of public finances in perspective - Cristina Ioana Antik (Agora International Journal of Economical Sciences (AIJES), 2019)
The emergence of public finances is due to objectively determined needs and causes, their main function being to procure the financial resources needed by the state to exercise its responsibilities and, in this way, to intervene in the economy and society in general. Public finances are necessary, subjectively and objectively, because they contribute to the accomplishment of the tasks and functions of the state, which could not be accomplished without the financial leverage. Public finances are indispensable related to the existence of the state, and to the role of the public sector in the economy. Thus, they express social relations, of economic nature that arise in the process of establishing and using public financial resources between the state, on the one hand, and the members of society on the other hand, in order to meet the general interest needs of society. Thus, the role of public finances is to meet needs of general interest, or collective needs.
Keywords: 330